Differential Diagnosis of Specific Reading and Writing Disorders: Speech, Language and Hearing Sciences Contributions - Giacheti, Celia Maria [UNESP]; da Silva, Nathani Cristina [UNESP]; De Andrade Lindau, Tâmara [UNESP] (Springer Nature, 2023)
The diagnosis of neurodevelopmental disorders, more specifically of disorders involving academic skills and related to school failure, is usually conducted by a multidisciplinary team. This differential diagnosis is one of the most difficult and complex tasks for health and education professionals. It should be conducted considering the clinical history, the presence or not of the same disorder in other family members, the set of manifestations, and the persistence of the condition after brief therapeutic intervention, now called response to intervention. This chapter aims to present concepts about the speech and language diagnostic process, with emphasis on specific learning disorders, more detailed on reading and writing, its main characteristics and frequency. We will also discuss manifestations that may differentiate reading and writing disorders from learning difficulties in these skills and, to illustrate, a case study will be presented.
Keywords: Differential diagnosis; Response to intervention; Specific learning disorders; Speech, Language and Hearing Sciences